Tourism and social media in the world: An empirical investigation - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
The study examines the relationship between tourism and social media from a cross section of 138 countries with data for the year 2012.The empirical evidence is based on Ordinary Least Squares, Negative Binomial and Quantile regressions. Two main findings are established. First, there is a positive relationship between Facebook penetration and the number of tourist arrivals. Second, Facebook penetration is more relevant in promoting tourist arrivals in countries where initial levels in tourist arrivals are the highest and low. The established positive relationship can be elucidated from four principal angles: the transformation of travel research, the rise in social sharing, improvements in customer service and the reshaping of travel agencies. This study explores a new dataset on social media. There are very few empirical studies on the relevance of social media in development outcomes.
Keywords: D83; O30; Z32; Z38; 330; Social Media; Tourism